Qi-Wei-Du-Qi-Wan and its major constituents exert an anti-asthmatic effect by inhibiting mast cell degranulation. (23rd May 2020) - Lin, Li-Jen; Wu, Chin-Jen; Wang, Shulhn-Der; Kao, Shung-Te
Abstract: Ethnopharmacological relevance: In Asia, Qi-Wei-Du-Qi-Wan (QWDQW) is a traditional Chinese medicine that has been used to treat chest tightness, cough, shortness of breath, night sweats, frequent urination and asthma. QWDQW is recorded in Yi Zong Yi Ren Pian (Medical Physician's Compilation), which was written by Yang Cheng Liu during the Qing Dynasty. Aim of the study: The traditional Chinese medicine QWDQW is composed of 7 ingredients and has been used in the treatment of asthma in Asia for hundreds of years. However, the mechanism through which QWDQW affects the immune system in the treatment of asthma is not known. Therefore, this study aimed to investigate whether QWDQW alleviates asthmatic symptoms in mice with chronic asthma induced by repeated stimulation with Dermatophagoides pteronyssinus (Der p) and to explore the underlying immune modulatory mechanism. Materials and methods: BALB/c mice were stimulated intratracheally (i.t.) with Der p (40 μl, 2.5 μg/μl) once weekly for 6 weeks. Thirty minutes prior to Der p stimulation, the mice were treated with QWDQW (0.5 g/kg and 0.17 g/kg) orally. Three days after the last stimulation, the mice were sacrificed, and infiltration of inflammatory cells, lung histological characteristics, gene expression of lung and serum total IgE were assessed. In other experiments, RBL-2H3 cells were stimulated with DNP-IgE/DNP-BSA and then treated with QWDQW, quercetin, β-carotene, luteolin or a mixture of the three chemicals (Mix13) for 30 min, and the effects of the drugs on RBL-2H3 cell degranulation after DNP stimulation were determined. Results: QWDQW significantly reduced Der p-induced airway hyperreactivity (AHR) and decreased total serum IgE and Der p-specific IgE levels. Histopathological examination showed that QWDQW reduced inflammatory cell infiltration and sputum secretion from goblet cells in the lungs. Gene expression analysis indicated that QWDQW reduced overproduction of IL-12、IFN-γ、IL-13、IL-4、RNATES、Eotaxin and MCP-1in lung. Additionally, QWDQW and Mix13 suppressed DNP induced RBL-2H3 degranulation, and the effect was maximal when quercetin, β-carotene and luteolin were administered together. Conclusion: These results indicate that QWDQW plays a role in suppressing excessive airway reaction and in specific immune modulation in a mouse model of chronic asthma and that QWDQW suppresses mast cell degranulation at defined doses of quercetin, β-carotene and luteolin. Graphical abstract: Image 1